2016
DOI: 10.1088/1751-8113/49/47/47lt01
|View full text |Cite
|
Sign up to set email alerts
|

Meta-conformal invariance and the boundedness of two-point correlation functions

Abstract: The covariant two-point functions, derived from Ward identities in direct space, can be affected by consistency problems and can become unbounded for large time-or spaceseparations. This difficulty arises for several extensions of dynamical scaling, for example Schrödinger-invariance, conformal Galilei invariance or meta-conformal invariance, but not for standard ortho-conformal invariance. For meta-conformal invariance in (1 + 1) dimensions, which acts as a dynamical symmetry of a simple advection equation, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…The conformal galilean generator Y 0 = −t∂ r − γ ∈ cga(1) is distinct from the ordinary Galilei generator Y 1/2 = −t∂ r − Mr ∈ sch(1) of the Schrödinger algebra, as these imply distinct transformations of the scaling operators.3 For the Schrödinger group, an analogous construction shows that the two-point functions are response functions[56,60,61,62]. The scaling form (1.15) of the meta-conformal correlator is the same as the special case z = 1 for the conformally co-variant two-time response function G(t, r) [21, eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The conformal galilean generator Y 0 = −t∂ r − γ ∈ cga(1) is distinct from the ordinary Galilei generator Y 1/2 = −t∂ r − Mr ∈ sch(1) of the Schrödinger algebra, as these imply distinct transformations of the scaling operators.3 For the Schrödinger group, an analogous construction shows that the two-point functions are response functions[56,60,61,62]. The scaling form (1.15) of the meta-conformal correlator is the same as the special case z = 1 for the conformally co-variant two-time response function G(t, r) [21, eq.…”
mentioning
confidence: 99%
“…We did not yet carry out explicitly the full algebraic procedure which should in the t ≫ z,z limit produce the non-diverging behaviour F ∼ t −2δ1 exp −2βγ 1 z+z t , see[62].…”
mentioning
confidence: 99%
“…6 The names are motivated by the greek prefixes o̺θo: right, standard and µετ α: of secondary rank. 7 Our results on the dynamical symmetries of the dle process, see propositions 3 and 4, require us to present here a more flexible definition than given in [34,35]. Table 2: Comparison of local ortho-conformal, conformal galilean and meta-1 conformal invariance, in (1 + 1)D. The non-vanishing Lie algebra commutators, the defining equation of the generators, the invariant differential operator S and the covariant two-point function is indicated, where applicable.…”
Section: Local Conformal Invariancementioning
confidence: 99%
“…The formulation of the meta-1 conformal Ward identities does require some care, since already the two-point function turns out to be a non-analytic function of the time-and space-coordinates. It can be shown that the covariant two-point correlator is [35]…”
Section: Local Conformal Invariancementioning
confidence: 99%
“…Readers may refer the recent works [71,72] (and references therein) for a detailed study of two-point functions.…”
mentioning
confidence: 99%